Effect of charge quantity on conduction mechanism of high- and low-resistance states during forming process in a one-transistor–one-resistor resistance random access memory. (6th April 2017) - Wu, Cheng-Hsien; Chang, Ting-Chang; Tsai, Tsung-Ming; Chang, Kuan-Chang; Chu, Tian-Jian; Pan, Chih-Hung; Su, Yu-Ting; Chen, Po-Hsun; Lin, Shih-Kai; Hu, Shih-Jie; Sze, Simon M.
Abstract: The forming process is a necessary and irreversible process to activate the resistance switching behavior in a resistance random access memory (RRAM) device. However, during the forming process, an overshoot current leads to device damage and causes inferior resistance switching characteristics; consequently, the process is considered to be a key factor in device degradation. In this paper, we find that a discontinuous conduction path can be formed by a pulse forming process such that the operation current can be reduced. We further investigate how the charge quantity during the forming process affects the carrier conduction mechanism of HRS, with all experiments and results demonstrated on one-transistor–one-resistor (1T1R) devices.